Solutions to higher Hamiltonians in the Toda hierarchies - Ferreira, L. A. [UNESP]; Londe, R. M. (AIP Publishing, 1990)
A method is presented for constructing the general solution to higher Hamiltonians (nonquadratic in the momenta) of the Toda hierarchies of integrable models associated with a simple Lie group G. The method is representation independent and is based on a modified version of the Lax operator. It constitutes a generalization of the method used to construct the solutions of the Toda molecule models. The SL(3) and SL(4) cases are discussed in detail. © 1990 American Institute of Physics.